Trapping of the Enoyl-Acyl Carrier Protein Reductase-Acyl Carrier Protein Interaction - Tallorin, Lorillee; Finzel, Kara; Nguyen, Quynh G.; Beld, Joris; La Clair, James J.; Burkart, Michael D. (Journal of the American Chemical Society, 2016)
An ideal target for metabolic engineering, fatty acid biosynthesis remains poorly understood on a molecular level. These carrier protein-dependent pathways require fundamental protein Protein interactions to guide reactivity and processivity, and their control has become one of the major hurdles in successfully adapting these biological machines. Our laboratory has developed methods to prepare acyl carrier proteins (ACPs) loaded with substrate mimetics and cross-linkers to visualize and trap interactions with partner enzymes, and we continue to expand the tools for studying these pathways. We now describe application of the slow-onset, tight-binding inhibitor triclosan to explore the interactions between the type II fatty acid ACP from Escherichia coli, AcpP,, and its corresponding enoyl-ACP Teductase, FabI. We show that the AcpP-triclosan complex demonstrates nM binding, inhibits in vitro activity, and can be used to isolate FabI in complex proteomes.